Time-dependent change in the microbiota structure of seminal stains exposed to indoor environmental - Gursoy, Nursena; Karadayi, Sukriye; Akmayan, Ilkguel; Karadayi, Beytullah; Ozbek, Tulin (SPRINGER, 2024)
Seminal stains acquired from fabric surfaces stand as pivotal biological evidence of utmost significance for elucidating sexual assault cases. The ability to determine the temporal aspect of a forensic incident via the analysis of a biological specimen found at the crime scene is crucial in resolving most cases. This study aimed to investigate the time-dependent change in the microbiota structure of human seminal stains exposed to indoor environmental conditions. Stains on polyester fabric generated using semen samples from five male volunteers were kept indoors for varying durations of up to 20 days, followed by sequencing of the V1-V9 regions of the 16S rRNA gene of the microbial DNA extracted from the stains. The acquired data provided the taxonomic composition, and microbial alterations across different days were examined. The most abundantly detected phyla in all samples were Firmicutes, Proteobacteria, and Bacteroidetes, and the relative abundances of bacteria were observed to change over time. Statistically significant changes at the species level were found for Treponema medium, Corynebacterium tuberculostearicum, Faecalibacterium prausnitzii, and Anaerostipes hadrus. Alterations observed in the samples between the analyzed time periods were investigated. The changes during the specified time periods were examined, identifying rare bacterial species that were initially present on certain days but later ceased to exist in the environment. Conversely, bacterial species that were absent before exposure but emerged at a later stage were also identified. The findings of this study demonstrate that species-level evaluations, in particular, can provide crucial insights into semen stain age.
Keywords: Next generation sequencing; Seminal stain; Microbiota; Microbial marker; BODY-FLUID IDENTIFICATION; SEXUAL ASSAULT; SEMEN STAINS; DNA; PERSISTENCE; BARRIERS; Legal Medicine